Development of Fluorophosphoramidate as a Biocompatibly Transformable Functional Group and its Application as a Phosphate Prodrug for Nucleoside Analogs. (29th April 2022) - Yoshida, Yuki; Zheng, Ti; Tanabe, Wataru; Tomoike, Fumiaki; Hashiya, Fumitaka; Suzuki, Tetsuro; Hirota, Shuto; Saiki, Yuriko; Horii, Akira; Hirayama, Akiyoshi; Soga, Tomoyosi; Kimura, Yasuaki; et al.
Abstract: Synthetic phosphate‐derived functional groups are important for controlling the function of bioactive molecules in vivo. Herein we describe the development of a new type of biocompatible phosphate analog, a fluorophosphoramidate (FPA) functional group that has characteristic P−F and P−N bonds. We found that FPA with a primary amino group was relatively unstable in aqueous solution and was converted to a monophosphate, while FPA with a secondary amino group was stable. Furthermore, by improving the molecular design of FPA, we developed a reaction in which a secondary amino group is converted to a primary amino group in the intracellular environment and clarified that the FPA group functions as a phosphate prodrug of nucleoside. Various FPA‐gemcitabine derivatives were synthesized and their toxicity to cancer cells were evaluated. One of the FPA‐gemcitabine derivatives showed superior toxicity compared with gemcitabine and its ProTide prodrug, which methodology is widely used in various nucleoside analogs, including anti‐cancer and anti‐virus drugs. Abstract : A new type of biocompatible phosphate analog, the fluorophosphoramidate (FPA) functional group, was developed. With the appropriate molecular design, the FPA group can be converted into the corresponding phosphate group in cells and is thus applicable as a phosphate prodrug for nucleoside analogs. One of the several FPA‐gemcitabine prodrugs showed effectively high toxicity toward pancreatic cancer cells, demonstrating the effectiveness of FPA‐based prodrugs.